CVD Polycrystalline Graphene as Sensing Film of Extended-Gate ISFET for Low-Drift pH Sensor. Issue 6 (23rd June 2021) - Zeng, Zhe; Wei, Wei; Li, Bochang; Gao, Ming; Yu, Zhi Gen; Chim, Wai Kin; Zhu, Chunxiang
Abstract : Drift phenomenon is a critical issue which causes reading errors in an ion sensitive field effect transistor (ISFET). The gate insulator surface modifications, such as hydration and buried site formation, which result from the diffusion of water species from the electrolyte, play the key roles in drift phenomenon. Here, the use of two-dimensional (2D) chemical vapor deposited (CVD) graphene as the sensing film of ISFETs to reduce drift has been proposed and investigated. Density functional theory calculations indicate good impermeability of the 2D graphene layer against water molecules, which may resist water species diffusion and contribute to low drift performance. The experimental measurements have shown that graphene acting as the extended-gate sensing film of ISFET exhibits a small drift rate of about 0.4 mV h −1 with a pH sensitivity of 33 mV pH −1 . The almost drift-free performance was measured immediately after device fabrication without any pre-immersion processes, indicating a superior stability of 2D CVD graphene.